(untitled) (Journal of Nepal Physical Society, 2024)
Graphene-like two-dimensional early transition metal carbides, nitrides, or carbonitrides with a metal-to-nonmetal atomic ratio of (n+1)/n called MXenes have many excellent electronic, optical, and electrochemical properties, such as metallicity, high electrical conductivity, larger charge density, high capacitance, efficient lithium, sodium, and potassium ions intercalability, etc. First-principles Density Functional Theory (DFT) calculations are performed to study the structural relationship of (Ti, Ta)2C MXenes to their electronic structure, magnetism, and optical properties. Calculations show carbide MXenes with a single transition metal, namely, titanium carbide (Ti2C) and tantalum carbide (Ta2C), and an ordered carbide MXene with double transition metals, namely, titanium tantalum carbide (TiTaC) are non-magnetic and metallic. The density of states at the Fermi level for each of (Ti, Ta)2C MXenes is dominated by the outermost d-orbitals of transition metal and the 2p orbital of carbon. The dielectric response function is a photon energy-dependent anisotropic quantity. In the static limit, the imaginary parts of the dielectric functions vanish for each of the (Ti, Ta)2C MXenes. However, the real part of the static dielectric constant is as high as two orders of magnitude for tantalum-containing MXenes and almost half of that for titanium-containing single transition metal carbide MXene.